2020
DOI: 10.1152/jn.00472.2019
|View full text |Cite
|
Sign up to set email alerts
|

When 90% of the variance is not enough: residual EMG from muscle synergy extraction influences task performance

Abstract: The muscle synergy hypothesis posits that the central nervous system simplifies motor control by grouping muscles into modules. Current techniques use dimensionality reduction, such that the identified synergies reconstruct 90% of the muscle activity. We show that residual muscle activity following such identification can have a large systematic effect on movements, even when the number of synergies approaches the number of muscles. Current synergy extraction techniques must therefore be updated to identify tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 47 publications
(53 reference statements)
2
27
0
Order By: Relevance
“…We found that a number of modules ranging from 3 to 5 reconstructed the original EMG for all subjects in each of the directions. While recent studies suggest that it is arbitrary to neglect a part of the reconstruction R 2 , which might be meaningful for movement generation (Barradas et al, 2019), these results are in good accordance with previous studies based on similar reconstruction criteria, which already demonstrated that, in a limited subset of movements of the upper-limb, a 17-muscle model can be reduced to the coordination of five motor modules with time-varying synergies (d’Avella et al, 2006). In the present experiment, starting from a comparable number of EMG channels, a limited number of modules, ranging from 3 to 5, was found for each of the considered mappings.…”
Section: Discussionsupporting
confidence: 89%
“…We found that a number of modules ranging from 3 to 5 reconstructed the original EMG for all subjects in each of the directions. While recent studies suggest that it is arbitrary to neglect a part of the reconstruction R 2 , which might be meaningful for movement generation (Barradas et al, 2019), these results are in good accordance with previous studies based on similar reconstruction criteria, which already demonstrated that, in a limited subset of movements of the upper-limb, a 17-muscle model can be reduced to the coordination of five motor modules with time-varying synergies (d’Avella et al, 2006). In the present experiment, starting from a comparable number of EMG channels, a limited number of modules, ranging from 3 to 5, was found for each of the considered mappings.…”
Section: Discussionsupporting
confidence: 89%
“…Aiming error doesn’t decline to less than 10% until the number of synergies equals the number of muscles (Aymar de Rugy et al, 2013 ). A similar conclusion was reached for a virtual force task involving 10 shoulder and elbow muscles moving a splinted forearm ( Barradas, Kutch, Kawase, Koike, & Schweighofer, 2020 ).…”
Section: How Might Humans Learn To Use Muscles?supporting
confidence: 65%
“…However, at the same time, the quality of the EMG signals reconstruction was slightly degraded. This finding demonstrated that a trade-off between the capability of the extracted muscle synergies to better describe the EMG signals variability and the task performance in terms of force reconstruction might exist and can be exploited to develop more intuitive myo-controllers that are mainly evaluated in the task space [19,41].…”
Section: Discussionmentioning
confidence: 99%
“…Few works have investigated the concept of functional synergies that are an initial attempt to link muscle synergies with task variables [19,[38][39][40]. However, as deeply discussed by Barradas et al [41] and Cristiano et al [19], functional synergies present some issues and limitations. After an extensive argumentation, Cristiano and his colleagues state that a novel required technique for muscle synergy extraction ".…”
Section: Introductionmentioning
confidence: 99%